Prevalence and Factors Associated with Anxiety Disorders Among Pregnant Women at Mulago National Referral Hospital, Uganda - Nabwire M; Nakimuli A; Nakasujja N; Migisha R; Kiggundu C (Dove Medical Press, 2024)
Mariam Nabwire,1 Annettee Nakimuli,1 Noeline Nakasujja,2 Richard Migisha,3,4 Charles Kiggundu1, † 1Department of Obstetrics and Gynecology, School of Medicine, Makerere University College of Health Sciences, Kampala, Uganda; 2Department of Psychiatry, School of Medicine, Makerere University College of Health Sciences, Kampala, Uganda; 3Uganda Public Health Fellowship Program, Uganda National Institute of Public Health, Kampala, Uganda; 4Department of Physiology, Mbarara University of Science and Technology, Mbarara, Uganda†Charles Kiggundu passed away on 29th December 2020Correspondence: Mariam Nabwire, Department of Obstetrics and Gynecology, School of Medicine, Makerere University College of Health Sciences, Kampala, Uganda, Tel +256 756600593 ; +256 775834405, Email nabwirem@yahoo.comBackground: Anxiety disorders in pregnancy are common and represent a global concern. However, data regarding the magnitude of anxiety among pregnant women in Uganda are limited, and yet, these data could pave way for implementing effective mitigation measures. We determined the prevalence of anxiety disorders and associated factors among pregnant women at Mulago Hospital Uganda.Methods: A cross-sectional study was conducted among pregnant women attending antenatal care clinic at Mulago Hospital between September and November 2015. Systematic sampling was used to enroll eligible women. An interviewer-administered demographic questionnaire and the Hamilton Anxiety Rating Scale for Antenatal Anxiety (HAMA-A) scale were used to assess demographic features and anxiety, respectively. Women with HAMA-A score ≥ 17 were considered to have anxiety disorder. Factors associated with anxiety disorders were determined using multivariate logistic regression.Results: A total of 501 pregnant women were enrolled into the study; the prevalence of anxiety disorders was 13% (n=65; 95% CI: 9.8- 15.7%). Factors that were significantly associated with anxiety disorders were low income of the participants (adjusted odds ratio [AOR]=2.65, 95% CI: 1.16- 6.06), bad relationship with spouse (AOR = 2.50, 95% CI: 1.01- 5.82) and history of hypertension in previous pregnancy (AOR = 4.17, 95% CI: 1.68- 10.37).Conclusion: Approximately one in ten women surveyed exhibited anxiety disorders. Anxiety disorders were associated with low-income levels, bad spousal relationships, and a history of hypertension during previous pregnancies. Multidisciplinary approaches that integrate mental health support, social services, and partner involvement may help address anxiety disorders in pregnancy and contribute to improved maternal and child outcomes.Keywords: anxiety disorders, pregnancy, antenatal care, Uganda